Association between male accesory gland infections and prostate cancer in Turkish men: A case–control study. (8th May 2018) - Aykan, S.; Temiz, M. Z.; Yilmaz, M.; Ulus, I.; Yuruk, E.; Muslumanoglu, A. Y.
Summary: It is well known that chronic inflammation contributes to several forms of human cancer. Although several studies have investigated the association between prostatitis and prostate cancer, there is a lack of specifically designed study about male accessory gland infections (MAGI) and prostate cancer co‐occurrence. We aimed to investigate this association with a case–control study in Turkish men. A total of 155 patients were enrolled to the study. After the pathological examination of the transrectal ultrasound‐guided prostate biopsy specimens, patients were divided the two groups as control and prostate cancer and the presence of MAGI was determined. Of 155 patients, 145 met inclusion criteria. In the prostate cancer group, MAGI diagnose was determined in 18 of 31 patients (58.06%), while it was determined in 25 of 114 (21.93%) patients in the control group ( p  = .001). A significant correlation between MAGI and pathological Gleason score also revealed ( p  = .0001). We demonstrated that men with MAGI have increased risk for the development of prostate cancer. Moreover, in this population, most of the prostate cancers tend to be clinically significant or high grade.